2021
DOI: 10.1007/s00204-021-03118-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent dynamics of metabolism in primary mouse hepatocytes

Abstract: The liver is one of the most sexually dimorphic organs. The hepatic metabolic pathways that are subject to sexual dimorphism include xenobiotic, amino acid and lipid metabolism. Non-alcoholic fatty liver disease and hepatocellular carcinoma are among diseases with sex-dependent prevalence, progression and outcome. Although male and female livers differ in their abilities to metabolize foreign compounds, including drugs, sex-dependent treatment and pharmacological dynamics are rarely applied in all relevant cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
(55 reference statements)
4
5
0
Order By: Relevance
“…Taking the liver as an example, we observed distinct separations in specific cell populations between females and males in hepatocytes ( fig. S8A-B ), consistent with previous research characterizing the liver as a “sexually dimorphic organ”( 35 , 36 ). This distinction is in line with known sex-specific variations in metabolic functions, such as superior alcohol clearance and lipid metabolism capabilities in males and heightened cholesterol metabolism abilities in females( 36 ).…”
Section: Main Textsupporting
confidence: 91%
See 1 more Smart Citation
“…Taking the liver as an example, we observed distinct separations in specific cell populations between females and males in hepatocytes ( fig. S8A-B ), consistent with previous research characterizing the liver as a “sexually dimorphic organ”( 35 , 36 ). This distinction is in line with known sex-specific variations in metabolic functions, such as superior alcohol clearance and lipid metabolism capabilities in males and heightened cholesterol metabolism abilities in females( 36 ).…”
Section: Main Textsupporting
confidence: 91%
“…S8A-B), consistent with previous research characterizing the liver as a "sexually dimorphic organ" (35,36). This distinction is in line with known sex-specific variations in metabolic functions, such as superior alcohol clearance and lipid metabolism capabilities in males and heightened cholesterol metabolism abilities in females (36). These sex-specific effects extend down to the sub-cluster level, as demonstrated by the identification of 73 sub-clusters displaying significant differential abundance between males and females across all age groups (fig.…”
supporting
confidence: 91%
“…In humans, it has been reported that PEMT activity is increased by estrogen, and therefore females may be resistant to choline deprivation (Leermakers et al, 2015). Sex-specific differences have been well characterized in both HCC (Natri et al, 2019; Takemoto et al, 2005) and MASLD, MASH, and HCC risk (Lonardo et al, 2019), as well as in mouse primary hepatocytes (Hochmuth et al, 2021), obese mice (Savva et al, 2022), rats (Lomas-Soria et al, 2018), and the zebrafish liver transcriptome (Zheng et al, 2013). At least some of the increased susceptibility to hepatocarcinogenesis in males is due to the effects of estrogen, which inhibits pro-tumorigenic IL-6 production (Naugler et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In these mice, fatty acid metabolism and pro-inflammatory genes were up-regulated 53 . Moreover, sexual dimorphic genes, such as Cyp1a2 and Esr1 (coding for a cytochrome P450 family member and an estrogen receptor, respectively) were de-regulated in mouse hepatocytes 54 . The liver is a sexually dimorphic organ 55 .…”
Section: Lamin A/c and Lamin-associated Proteins Dysfunction In Hepatocytesmentioning
confidence: 99%